Methodological notes on the anthropology of public action (Raíces: Revista de Ciencias Sociales y Políticas, 2020)
The study of public policies has traditionally been a field of study of political science. Using as  starting point the theoretical-methodological proposal of the anthropology of public action proposed by Rodríguez Castillo, in which public policies become understood as an object of culture, a new fertile field is opened to enter this theme starting of anthropological studies. Based on this proposal, an investigation has been carried out on the Public Security apparatus in El Salvador and another on the Cultural Policy of the University of El Salvador. This approach positioned researchers in a different ethnographic reality that necessarily led to the application of a specific methodology for the study of public action.
Keywords: anthropology; action; politics; public; ethnography